Head Circumference Profile of Infants Aged 9–15 Months Related to Intelligence in Sukabumi and Cirebon - Safira Kansa Madyasari; Meita Dhamayanti; Dini Saraswati Handayani; Lani Gumilang; Fardila Elba (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Golden period is any child's period needing attention for their growth, and it would cause permanent damages if not utilized well. Early detection of an infant’s growth needs to be implemented with anthropometric measurements, Head Circumference (HC) as one of the nutritional status references. HC correlates with brain volume, and it indicates an infant's intelligence. This study aims to discover the HC measure of infants aged 9-15 months related to their intelligence in the Sukabumi City and Cirebon Regency. The design of this study was a non-experimental quantitative design with a descriptive study approach and cross- sectional method. The data were taken by measuring the infants’ HC directly and interviewing infants’ mothers. The results of the examination were confirmed and classified based on WHO charts, namely the z-score chart. The results showed that the HC status of most of the infants (86.36%) in Sukabumi City and Cirebon Regency could be categorized in the normal category. The results of the study were mostly in good HC status, but so me infants had growth problems, such as 13.64% of infants were included in microcephaly based on head circumference according to age that could have been caused by various factors such as nutrition, and this may be able to affect the intelligence of these children in the future.